Detection of trace aflatoxin M1 in human urine using a commercial ELISA followed by HPLC. (2nd January 2017) - Schwartzbord, Jeremy; Severe, Linda; Brown, Dan
Abstract: Aflatoxin is a liver carcinogen, and rapid, inexpensive methods to detect its urinary biomarkers are needed. We used a commercial enzyme-linked immuno-sorbent assay (ELISA) for aflatoxin M1 in urine (Helica Biosystems) to test 52 Haitian samples. Using this ELISA, we detected traces above the limit of detection (0.2 ng/ml urine) but below the limit of quantitation (0.4 ng/ml) in 14 samples. Liquid chromatography of all 52 Haitian urine samples revealed that only 11 had quantifiable AFM1 (mean: 29.5 pg/ml, standard error: 10.8, range: 2.94–96.5 pg/ml). The Helica ELISA may have detected forms of aflatoxin other than AFM1 in the Haitian samples, or matrix enhancement may have affected results at low AFM1 concentrations. This ELISA may serve as an initial, qualitative indicator of aflatoxin exposure for epidemiological purposes. But this method's utility as a precise and specific indicator of AFM1 concentrations will require additional refinement and validation.